2015
DOI: 10.4236/jtr.2015.33010
|View full text |Cite
|
Sign up to set email alerts
|

The Non-Enzymatic Antioxidant and Level of Oxidative Stress of Tuberculosis Patients in Selected Treatment Center in Addis Ababa Ethiopia

Abstract: G. Gebretsadik et al. 64volunteers. In contrast to this, the MDA value was significantly higher both in the newly diagnosed TB patients and TB patients who completed treatment than in healthy volunteers suggesting higher degree of oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…[ 11 ]. According to Ethiopian studies, the magnitude of undernutrition in this study was still lower than in studies conducted in Ambo, West Ethiopia (63.5 percent) [ 14 ], Metema (51 percent) [ 15 ], and Gamo Goffa Zone, South Ethiopia (50 percent) [ 19 ] but higher than in studies conducted in Addis Ababa, Ethiopia (27.15 percent) [ 17 ]. The difference may be explained by differences in the socioeconomic status, study area, lifestyle, feeding pattern and economic status of the countries, and sample size of the study.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…[ 11 ]. According to Ethiopian studies, the magnitude of undernutrition in this study was still lower than in studies conducted in Ambo, West Ethiopia (63.5 percent) [ 14 ], Metema (51 percent) [ 15 ], and Gamo Goffa Zone, South Ethiopia (50 percent) [ 19 ] but higher than in studies conducted in Addis Ababa, Ethiopia (27.15 percent) [ 17 ]. The difference may be explained by differences in the socioeconomic status, study area, lifestyle, feeding pattern and economic status of the countries, and sample size of the study.…”
Section: Discussioncontrasting
confidence: 55%
“…Few studies revealed that the magnitude of undernutrition among TB patients ranged from 52 to 90% in lowincome countries other than SSA countries [6][7][8][9], 43-78% in SSA [10][11][12][13] and 27.2% to 84.4%, [14][15][16][17][18][19] in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…If the levels of free radicals and ROS exceed the reduction level of the antioxidant system, the antioxidant capacity of the body decreases, resulting in oxidative damage to biological macromolecules [39]. A large number of studies have shown that free radicals can cause peroxidative damage to cell membrane lipids and produce MDA which involved in attacking polyunsaturated fatty acids in biological cell membranes, further triggering lipid peroxidation, leading to more severe oxidative stress damage [40,41]. However, many studies have shown that probiotics have excellent antioxidant functions.…”
Section: Discussionmentioning
confidence: 99%
“…This group of fat soluble antioxidants has been shown to benefit respiratory health due to their ability to scavenge reactive oxygen species "ROS" and reduce oxidative stress (11). Vitamin C is the major water soluble antioxidant and a powerful inhibitor of lipid peroxidation and regenerates vitamin E in lipoproteins and membranes (12).…”
Section: Original Articlementioning
confidence: 99%